Multicriteria decision analysis for the evaluation of water quality improvement and ecosystem service provision. (14th September 2016) - McInnes, Robert; Smith, Graham; Greaves, Julian; Watson, David; Wood, Nikki; Everard, Mark
Abstract: Water and land management decisions require consideration of multiple factors. Multicriteria decision analysis (MCDA) provides a structured, auditable and transparent tool that helps inform and add rigour to multioption decisions. MCDA was used in a payment for ecosystem services (PES) project to evaluate options for delivering good ecological status in Tortworth Brook, Gloucestershire, UK. Following a process of stakeholder engagement, final options considered were: (1) doing nothing; (2) modifying existing sewage treatment works; (3) a single integrated constructed wetland (ICW) targeting multiple ecosystem service outcomes; and (4) catchment wide multiple ICWs. The analysis concluded that the 'do nothing' option and modifying the existing works are both likely to provide poor utility and value for money. Both ICW options offered the greatest utility in terms of optimising the benefits to all stakeholders.